How European primary care practitioners think the timeliness of cancer diagnosis can be improved: a thematic analysis - Harris, Michael; Thulesius, Hans; Neves, Ana Luísa; Harker, Sophie; Koskela, Tuomas; Petek, Davorina; Hoffman, Robert; Brekke, Mette; Buczkowski, Krzysztof; Buono, Nicola; Costiug, Emiliana; Dinant, Geert-Jan; et al. (BMJ Open, 2019)
BackgroundNational European cancer survival rates vary widely. Prolonged diagnostic intervals are thought to be a key factor in explaining these variations. Primary care practitioners (PCPs) frequently play a crucial role during initial cancer diagnosis; their knowledge could be used to improve the planning of more effective approaches to earlier cancer diagnosis.ObjectivesThis study sought the views of PCPs from across Europe on how they thought the timeliness of cancer diagnosis could be improved.DesignIn an online survey, a final open-ended question asked PCPs how they thought the speed of diagnosis of cancer in primary care could be improved. Thematic analysis was used to analyse the data.SettingA primary care study, with participating centres in 20 European countries.ParticipantsA total of 1352 PCPs answered the final survey question, with a median of 48 per country.ResultsThe main themes identified were: patient-related factors, including health education; care provider-related factors, including continuing medical education; improving communication and interprofessional partnership, particularly between primary and secondary care; factors relating to health system organisation and policies, including improving access to healthcare; easier primary care access to diagnostic tests; and use of information technology. Re-allocation of funding to support timely diagnosis was seen as an issue affecting all of these.ConclusionsTo achieve more timely cancer diagnosis, health systems need to facilitate earlier patient presentation through education and better access to care, have well-educated clinicians with good access to investigations and better information technology, and adequate primary care cancer diagnostic pathway funding.